Negative electrode material, its manufacturing method, and lithium ion battery

By designing the chamber and hole structure in the carbon shell layer in the negative electrode material, the problem of volume expansion in lithium-ion batteries is solved, the expansion resistance and energy density of the material are improved, and the use of adhesive is reduced.

JP2025503824AActive Publication Date: 2025-02-06BTR NEW MATERIAL GRP CO LTD
View PDF 20 Cites 0 Cited by

Patent Information

Application Number
JP2023567071
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-12-26
Filing Date
2023-09-08
Publication Date
2025-02-06
Estimated Expiration
2043-09-08

AI Technical Summary

Technical Problem

Due to insufficient mechanical properties in lithium-ion batteries, existing negative electrode materials cannot effectively suppress volume expansion, resulting in reduced energy density and low utilization efficiency.

Method used

The negative electrode material design is adopted that includes a carbon shell layer, with a chamber and a hole in the carbon shell layer, and the chamber is filled with silicon material, which releases or absorbs gas through the holes to resist volume changes caused by lithium insertion.

Benefits of technology

The expansion resistance and circulation performance of the negative electrode material are improved, the energy density and utilization efficiency are enhanced, and the dependence on the adhesive is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503824000001_ABST
    Figure 2025503824000001_ABST
Patent Text Reader

Abstract

The present application relates to a negative electrode material and a method for producing the same, and to a lithium ion battery. [Solution] The negative electrode material includes a carbon material, the carbon material includes a carbon shell layer, and the carbon material has a chamber inside, the chamber is formed so as to be surrounded by the carbon shell layer, and the carbon shell layer has holes, and at least some of the holes penetrate the carbon shell layer. In the negative electrode material of the present application, the carbon material has a chamber located inside and holes located in the carbon shell layer, so that the negative electrode material can secure a sufficient space to withstand the expansion stress of lithium insertion, and improve the expansion resistance and cycle performance of the negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to a Chinese patent application filed with the China Patent Office on December 26, 2022, bearing application number 202211679854.8 and entitled "Negative electrode material and its manufacturing method, and lithium ion battery", the entire contents of which are incorporated herein by reference.

[0002] The present application relates to the technical field of negative electrode materials, and more particularly to negative electrode materials and manufacturing methods, and lithium ion batteries. [Background technology]

[0003] Porous carbon anode materials are one of the most important materials for improving the cycle expansion performance of lithium-ion batteries. Conventional common porous carbon anode materials realize the support for lithium by their large internal chamber or pore structure, thereby suppressing the volume expansion. These porous carbon materials are usually synthesized by simple high-temperature carbonization, and the porous structure directly formed by high-temperature carbonization has a discontinuous graphite crystal lattice structure, and such a structure reduces the mechanical properties of the carbon material itself and the van der Waals forces between the carbon material particles derived from graphite π-π stacking, and the particle pores and gaps between the particles cannot withstand the expansion stress of lithium insertion, so that extra adhesive needs to be added to the anode material, which reduces the energy density of the anode porous carbon material to a certain extent. At the same time, porous carbon anode materials often require thick pore walls to provide sufficient mechanical strength, which reduces the utilization efficiency of carbon and is unfavorable to the capacity.

[0004] Therefore, there is currently an urgent need to develop a negative electrode material that has high capacity and low expansion. Summary of the Invention [Problem to be solved by the invention]

[0005] The present application provides a negative electrode material, a manufacturing method thereof, and a lithium ion battery. The negative electrode material of the present application can improve the carbon utilization efficiency in the material, further improve the capacity and cycle ability of the material, and has excellent expansion resistance. [Means for solving the problem]

[0006] In order to achieve the above objective, the first technical proposal of the present application is as follows: an embodiment of the present application provides a negative electrode material, the negative electrode material includes a carbon material, the carbon material includes a carbon shell layer, and the carbon material has a chamber inside, the chamber is formed to be surrounded by the carbon shell layer, and the carbon shell layer has holes, and at least some of the holes penetrate the carbon shell layer.

[0007] The second technical solution of the present application is as follows: the embodiment of the present application provides a method for manufacturing a negative electrode material; A mixture including a silicon-oxygen source supported by metal catalyst particles and a carbon source is subjected to a first heat treatment to catalyze graphitization of the carbon source to obtain a first precursor; the first precursor is etched to obtain a second precursor, the etchant of the etching process being an oxidizing acid; The method includes a step of reducing at least a portion of the silicon oxygen source in the second precursor to a silicon material to obtain a negative electrode material.

[0008] The third technical solution of the present application is as follows: An embodiment of the present application provides a lithium ion battery, the lithium ion battery comprising an anode material according to the first aspect or anode material produced by the method according to the second aspect. Effect of the Invention

[0009] The technical means of the present invention have at least the following beneficial effects:

[0010] In the negative electrode material of the present application, the carbon material has a chamber located inside the carbon shell layer and a hole located in the carbon shell layer, and the presence of the chamber and the hole makes the carbon material a porous hollow housing, and such a structure can ensure sufficient space when the filled silicon material expands. When the silicon material expands and presses the carbon material, the carbon material discharges the internal gas or electrolyte through the hole on the carbon shell layer to form a distortion in order to withstand the expansion stress of lithium insertion, and when the silicon material releases lithium and shrinks, the distorted carbon material absorbs the gas or electrolyte through the hole on the carbon shell layer to recover its shape, thereby improving the expansion resistance and cycle performance of the negative electrode material.

[0011] The present invention provides a method for producing a first precursor by subjecting a mixture containing a silicon-oxygen raw material supported on catalytic metal particles and a carbon source to a first heat treatment, the carbon source being graphitized and decomposed during the first heat treatment to produce carbon atoms, some of which can dissolve inside the catalytic metal particles and dissolve until saturation and precipitate on the catalyst surface, and the precipitated carbon atoms grow into a carbon shell layer, and some of which can grow along the surface of the metal particles through the catalytic action of the catalytic metal particles to form a carbon shell layer, forming a structure in which the catalytic metal particles are sealed inside the carbon shell layer, while the silicon-oxygen raw material has poor catalytic ability for the carbon source material, so that the silicon-oxygen raw material is distributed outside the carbon shell layer and dispersed among the metal particles enclosed in the carbon shell layer, thereby obtaining a first precursor. Then, the first precursor is etched, and the catalytic metal particles inside the carbon shell layer are etched to form a chamber; at the same time, the oxidizing acid etched reacts with the defects in the carbon shell layer to form bonds such as CO, C=O, CN and CS to form holes, forming a porous carbon material (i.e., the second precursor) with a hollow space inside; and finally, at least a part of the silicon-oxygen raw material in the second precursor is reduced to a silicon material to obtain a negative electrode material. In the manufacturing method of the present application, under the first heat treatment conditions, the carbon source is catalytically grown into a shell layer structure through the metal catalytic particles, and the carbon shell layer structure has a chamber inside through the etching process, and the carbon shell layer has a hole, thereby improving the expansion resistance of the material; finally, in the present application, there is no need to etch the silicon-oxygen raw material, and the silicon-oxygen raw material is directly reduced to a silicon material, which reduces the waste of the silicon-oxygen raw material and improves the capacity of the negative electrode material. [Brief description of the drawings]

[0012] The present application will now be further described with reference to the drawings and examples. [Figure 1] FIG. 1 is a schematic diagram showing the configuration of a negative electrode material according to the present application. [Diagram 2] FIG. 2 is a schematic diagram showing a cross-sectional structure of a carbon material. [Diagram 3] 1 is a flowchart for producing a negative electrode material according to the present application. [Figure 4]FIG. 2 is a diagram showing a preparation process for obtaining a first precursor by performing a first heat treatment on a silicon / oxygen raw material supported on metal catalyst particles and a carbon source according to the present application. [Diagram 5] FIG. 1 is a process diagram for producing a silicon-oxygen raw material carrying metal catalyst particles according to the present invention. [Figure 6] FIG. 2 is a diagram showing the manufacturing process of the silicon-oxygen raw material carrying metal catalyst particles according to the present invention. [Figure 7] FIG. 2 is a diagram showing a manufacturing process for obtaining a second precursor by etching a first precursor according to the present application. [Figure 8] FIG. 11 is a manufacturing process diagram for obtaining a negative electrode material by mixing a second precursor and a reducing agent and performing a third heat treatment. [Figure 9] FIG. 2 is a schematic diagram showing a simulation configuration of the negative electrode material according to the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In order to better understand the technical solution of the present invention, the following detailed description of the embodiments of the present invention is given with reference to the accompanying drawings.

[0014] It should be clear that the described embodiments are only some of the embodiments of the present application, but not all of the embodiments. Based on the embodiments of the present application, all other embodiments that a person skilled in the art can make without any creative effort fall within the scope of protection of the present application.

[0015] The terms used in the embodiments of the present application are used only to describe specific embodiments and are not intended to limit the present invention. The singular forms "a," "the," and "the" used in the embodiments and claims of the present invention are intended to include the plural forms unless the context clearly indicates otherwise.

[0016] It should be understood that the term "and / or" used herein is only for describing the relation between related objects, and indicates that three kinds of relations can exist. For example, A and / or B can indicate three kinds of situations, namely, A exists alone, A and B exist together, and B exists alone. In addition, the character " / " in this specification generally indicates that the related objects before and after are in an "or" relationship.

[0017] The present application provides an anode material 10, and as shown in FIG. 1 , the anode material 10 includes a carbon material 1, which includes a carbon shell layer 12, and a chamber 11 is formed inside the carbon material 1, and the chamber 11 is formed to surround the carbon shell layer 12. The carbon shell layer 12 has pores 13, and at least some of the pores 13 penetrate the carbon shell layer 12.

[0018] In the above technical solution, in the anode material 10 of the present application, the carbon material 1 has a chamber 11 located inside the carbon shell layer 12 and a hole 13 located in the carbon shell layer 12. Due to the presence of the chamber 11 and the hole 13, the carbon material 1 becomes a hollow housing having porosity. This structure can reserve sufficient space when the filled silicon material expands. When the silicon material expands and presses the carbon material 1, the carbon material 1 discharges the internal gas or electrolyte through the hole 13 on the carbon shell layer 12 to withstand the expansion stress of lithium insertion, and forms a distortion. When the silicon material releases lithium and contracts, the distorted carbon material 1 absorbs the gas or electrolyte through the hole 13 on the carbon shell layer 12 to recover its shape, so that the anode material 10 can reserve sufficient space to withstand the expansion stress of lithium insertion, improving the expansion resistance and cycle performance of the anode material 10.

[0019] Furthermore, the negative electrode material 10 further includes a silicon material 2, and the silicon material 2 is distributed in the carbon material 1. The carbon material 1 ensures a sufficient space for the expansion of the filled silicon material 2, and the filled silicon material 2 can improve the usable space of the negative electrode material 10 and the capacity of the negative electrode material 10.

[0020] Preferably, at least a portion of the silicon material 2 is distributed between the carbon shell layers 12 .

[0021] As shown in FIG. 2 , in one embodiment, the carbon material 1 is spherical, and the carbon shell layer 12 includes a graphitized carbon material 14, which has a layered structure. The layered structure of the graphitized carbon material 14 is arranged in a layered manner along the radial direction of the carbon material 1. Therefore, the carbon shell layer 12 has excellent elastic modulus and tensile strength, which helps the carbon shell layer 12 to shrink and recover its shape without decomposition when strain is generated.

[0022] Referring to FIG. 2 which is a schematic diagram showing the configuration of carbon material 1, the stacking direction of the layered structure of graphitized carbon material 14 extends along the radial direction of carbon material 1, i.e., the length direction of the layered structure of graphitized carbon material 14 is perpendicular to the radial direction of carbon material 1, and the thickness direction (i.e., stacking direction) of graphitized carbon material 14 is perpendicular to the extension direction of carbon shell layer 12 and coincides with the radial direction of carbon material 1.

[0023] The graphitized carbon material includes at least one of graphite and graphene. Preferably, the graphitized carbon material is graphene, and the number of layers in the layered structure of graphene is less than 20, specifically, it may be 1 layer, 2 layers, 3 layers, 5 layers, 8 layers, 10 layers, 12 layers, 15 layers, 18 layers, or 19 layers, etc., and of course, it may be other values ​​within the above range, and is not limited here.

[0024] In one embodiment, the graphitizable carbon material is graphite, and the graphite is a stack of multiple layers of graphene, and the number of layers in the layered structure in the graphite is 20 or more, specifically, 20 layers, 30 layers, 50 layers, 80 layers, 100 layers, 120 layers, 150 layers, 180 layers, or 200 layers, etc., and of course other values ​​within the above range are also possible, and are not limited herein.

[0025] In some embodiments, some of the silicon material may be located in the chambers 11 and / or holes 13 to improve the capacity of the anode material 10.

[0026] In some embodiments, layered graphite (layered graphite is not shown in the drawings) is provided between the carbon materials 1, and the presence of the layered graphite structure strengthens the conductive network of the negative electrode material 10, thereby improving the conductivity of the negative electrode material 10.

[0027] In some embodiments, the median diameter of the carbon material 1 is 5 nm to 200 nm. Specifically, the median diameter of the carbon material 1 may be, for example, 5 nm, 10 nm, 20 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0028] In some embodiments, the thickness of the carbon shell layer 12 is 1.2 nm to 5.2 nm. Specifically, the thickness of the carbon shell layer 12 may be, for example, 1.2 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 5 nm, 5.2 nm, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0029] The thickness of the carbon shell layer 12 in the present application is 1.2 nm to 5.2 nm, and the graphitized carbon material 14 has a layered structure. This indicates that the carbon shell layer 12 in the present application has a certain rigidity and a certain elasticity, and can resist the volume expansion of the material due to lithium insertion.

[0030] In some embodiments, the negative electrode material exhibits a Raman spectrum obtained by Raman spectroscopy using a measurement light source having a wavelength of 532 nm and a Raman spectrum having a wavelength of 1300 cm -1 ~1400cm -1 The D band was observed at 1500 cm -1 ~1600cm -1 The G band was observed at 100 nm, and the D band peak intensity was I D and G-band peak intensity I G Comparison with I G / I D is greater than 0.5. Specifically, I G / ID may be 0.6, 0.7, 0.8, 0.9, etc., and may of course be other values ​​within the above range, and the present application is not limited thereto. Within the above limited range, the graphitization degree of the negative electrode material of the present application is high, and there is a strong π-π stacking van der Waals force between the carbon materials 1, and such a structure can resist the expansion stress caused by lithium insertion, thereby exerting the lithium insertion ability of the pores between the carbon materials 1, and improving the utilization efficiency of carbon.

[0031] In some embodiments, the average inner diameter of chamber 11 is 3.8 nm to 198.8 nm. Specifically, the average inner diameter of chamber 11 may be, for example, 3.8 nm, 10 nm, 30 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, 198.8 nm, etc., and of course may be other values ​​within the above range, and the present application is not limited thereto, and it is understood that carbon material 1 is spherical, chamber 11 is also spherical, and the average inner diameter of chamber 11 refers to the average value of the diameters of the inner circles in spherical chamber 11.

[0032] In some embodiments, the average pore diameter of the pores 13 is 0.42 nm to 2 nm. Specifically, the average pore diameter of the pores 13 may be 0.42 nm, 0.5 nm, 1 nm, 1.5 nm, 1.8 nm, 2 nm, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0033] In some embodiments, the distance between adjacent carbon materials 1 is 0 nm to 40 nm. Specifically, the distance between adjacent carbon materials 1 may be, for example, 0.34 nm, 1 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, etc., and of course may be other values ​​within the above range, and the present application is not limited thereto. In the negative electrode material 10 of the present application, if the distance between adjacent carbon materials 1 is short, it is advantageous to reduce the formation of bulk lithium in the lithium insertion process of the material and the leakage of silicon material 2 in the lithium release process, and it is understood that the distance between some adjacent carbon materials 1 may be 0 nm.

[0034] In some embodiments, the sphericity of the carbon material 1 is 0.6 to 1.0, specifically, the sphericity of the carbon material 1 may be 0.6, 0.7, 0.8, 0.9, 1.0, etc., and may of course be other values ​​within the above range, and the present application is not limited thereto. The carbon material 1 of the present application has a high sphericity, which is advantageous for improving the processing performance of the material.

[0035] In some embodiments, the mass ratio of the silicon material 2 in the negative electrode material 10 is 5% to 80%. Specifically, the mass ratio of the silicon material 2 in the negative electrode material 10 may be, for example, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0036] In some embodiments, the median diameter of the silicon material 2 is 1 nm to 15 nm. For example, the median diameter of the silicon material 2 may be 1 nm, 3 nm, 5 nm, 8 nm, 10 nm, 12 nm, 14 nm, 15 nm, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0037] In some embodiments, the silicon material 2 comprises at least one of crystalline silicon and amorphous silicon.

[0038] In some embodiments, the elastic modulus of the carbon material 1 is 0.1 TPa to 0.8 TPa. Specifically, the elastic modulus of the carbon material 1 may be, for example, 0.1 TPa, 0.2 TPa, 0.3 TPa, 0.4 TPa, 0.5 TPa, 0.6 TPa, 0.7 TPa, 0.8 TPa, etc., and of course may be other values ​​within the above range and is not limited in the present application. When the elastic modulus of the carbon material 1 is 0.1 TPa or less, the carbon material 1 is easily disintegrated, and when the elastic modulus of the carbon material 1 is 0.8 TPa or more, the rigidity of the carbon material 1 increases and it is difficult to provide space for expansion due to lithium insertion.

[0039] In some embodiments, the tensile strength of the carbon material 1 is 15 GPa to 110 GPa, specifically, the tensile strength of the carbon material 1 may be, for example, 15 GPa, 30 GPa, 50 GPa, 60 GPa, 80 GPa, 100 GPa, and 110 GPa, and of course, may be other values ​​within the above range, and the present application is not limited thereto. Within the above range, the carbon material 1 of the present application has excellent mechanical properties, because the thickness of the shell layer of the carbon material 1 in the present application is thin, the degree of graphitization is high, and the distance between the carbon materials 1 is short, so that the π-π stacking van der Waals force is strong, and therefore the gap structure between the carbon materials 1 has good stability, and such stability can resist the expansion stress caused by lithium insertion, and exert the lithium insertion ability of the pores between the particles, thereby improving the utilization efficiency of carbon. If the tensile strength of the carbon material 1 is less than 15 GPa, the carbon material is easily crushed during lithium insertion and expansion, and if the tensile strength of the carbon material 1 is more than 110 GPa, it is difficult to provide space for lithium insertion and expansion.

[0040] In some embodiments, the porosity of the carbon material 1 is 65% to 96%, and specifically, the porosity of the carbon material 1 may be, for example, 65%, 70%, 75%, 80%, 85%, 90%, 96%, etc., and of course, may be other values ​​within the above range, and is not limited here in the present application, and it is understood that the porosity of the carbon material 1 refers to the volume ratio of the chambers 11 and the holes 13 in the carbon material 1.

[0041] In some embodiments, the porosity of the negative electrode material 10 is 7% to 50%, and specifically, the porosity of the negative electrode material 10 may be, for example, 7%, 10%, 15%, 20%, 30%, 40%, 50%, etc., and of course, may be other values ​​within the above range, and is not limited in the present application, and it is understood that the porosity of the negative electrode material 10 refers to the volume ratio of the voids between the chamber 11, the hole 13, and the carbon material 1 to the negative electrode material 10. Since the porosity of the negative electrode material 10 of the present application is high, the negative electrode material 10 has excellent expansion resistance.

[0042] In some embodiments, the π-π stacking van der Waals force between adjacent carbon materials 1 is 1 kJ / mol to 50 kJ / mol, specifically, the π-π stacking van der Waals force between adjacent carbon materials 1 is 1 kJ / mol, 5 kJ / mol, 10 kJ / mol, 20 kJ / mol, 30 kJ / mol, 40 kJ / mol, and 50 kJ / mol, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto. By having a strong π-π stacking van der Waals force between the carbon materials 1 of the present application, the gap between the carbon materials 1 can withstand the expansion stress of lithium insertion, and the energy density of the negative electrode material 10 can be improved without adding an additional adhesive.

[0043] The present application further provides a method for producing the above-mentioned negative electrode material 10. As shown in FIG. 3, the present application provides a flowchart for producing the negative electrode material 10, A mixture including a silicon-oxygen raw material supported by metal catalyst particles and a carbon source is subjected to a first heat treatment to catalyze graphitization of the carbon source to obtain a first precursor; The first precursor is etched to obtain a second precursor, the etching agent of the etching process comprising an oxidizing acid; The method includes reducing at least a portion of the silicon oxygen source in the second precursor to a silicon material to obtain the anode material 10.

[0044] In the above technical solution, the present application provides a first heat treatment for a mixture containing a silicon-oxygen raw material supported on catalytic metal particles and a carbon source, so that the carbon source is graphitized and decomposed during the first heat treatment to produce carbon atoms, some of the carbon atoms can be dissolved inside the catalytic metal particles, and dissolved until saturation and precipitate on the catalyst surface, and the precipitated carbon atoms grow into the carbon shell layer 12, and other carbon atoms can grow along the surface of the metal particles through the catalytic action of the catalytic metal particles to form the carbon shell layer 12, forming a structure in which the catalytic metal particles are sealed inside the carbon shell layer 12; on the other hand, the silicon-oxygen raw material has poor catalytic ability for the carbon source material, so that the silicon-oxygen raw material is distributed outside the carbon shell layer 12 and dispersed among the metal particles sealed in the carbon shell layer 12 to obtain a first precursor. Then, the first precursor is etched, the catalytic metal particles inside the carbon shell layer are etched to form the chamber 11, and at the same time, the oxidizing acid in the etching process causes an oxidation-reduction reaction with the defects in the carbon shell layer 12, gradually peeling off the carbon atoms to form the holes 13, and at the end of the oxidation-reduction process, bonds such as CO, C=O, CN and CS are formed on the edge of the holes to form a porous carbon material 1 (i.e., the second precursor) having the chamber 11 inside; and finally, at least a part of the silicon oxygen raw material in the second precursor is reduced to a silicon material to obtain the anode material 10. In the manufacturing method of the present application, under the first heat treatment conditions, the carbon source is catalytically grown into a shell layer structure through the metal catalytic particles, and the shell layer structure has a large pore volume and lithium insertion ability, and further, the carbon shell layer 12 structure has a chamber 11 inside through the etching process, and the carbon shell layer 12 has holes 13, thereby improving the expansion resistance performance of the material; finally, in the present application, there is no need to etch the silicon oxygen raw material, and the silicon oxygen raw material is directly reduced to a silicon material 2, which reduces the waste of the silicon oxygen raw material and improves the capacity of the anode material 10.

[0045] The production method of the present invention will be specifically described below with reference to examples. In step S100, the mixture including the metal catalyst particle-supported silicon-oxygen source and the carbon source is subjected to a first heat treatment to catalyze the graphitization of the carbon source to obtain a first precursor, as shown in Figure 4. In some embodiments, the carbon source includes a gas phase carbon source and a solid phase carbon source.

[0046] In some embodiments, the gas phase carbon source comprises at least one of methane, ethane, and acetylene.

[0047] In some embodiments, the solid carbon source includes at least one of pitch, glucose, sucrose, cellulose, glycine, alanine, and phenylalanine. When the first heat treatment is performed using a solid carbon source, the solid carbon source has poor uniformity compared to a gaseous carbon source, so that the local carbon source becomes excessive, and a layered graphite structure is formed between the carbon material 1. The existence of the layered graphite structure can strengthen the conductive network of the negative electrode material 10 and improve the conductivity of the negative electrode material 10.

[0048] In some embodiments, the mass ratio of the solid-phase carbon source to the metal catalyst particles is 1: (10 to 10000). Specifically, the mass ratio of the solid-phase carbon source to the metal catalyst particles may be, for example, 1:10, 1:50, 1:100, 1:500, 1:1000, 1:5000, and 1:10000, and of course, may be other values ​​within the above range, and the present application is not limited thereto. Within the above range, the amount of metal catalyst particles added is large, and the carbon source contributes to generating a thin shell layer structure on the surface of the metal catalyst particles. If the mass ratio of the solid-phase carbon source to the metal catalyst particles is greater than 1:10, excessive amorphous carbon is generated, which is disadvantageous to improving the performance of the material. If the mass ratio of the solid-phase carbon source to the metal catalyst particles is less than 1:10000, the amount of carbon source added is too small, and the carbon source cannot completely cover the metal catalyst particles.

[0049] In some embodiments, the flow rate of the gaseous carbon source is 10sccm to 250sccm, specifically, the flow rate of the gaseous carbon source is 10sccm, 30sccm, 50sccm, 100sccm, 150sccm, 200sccm, 250sccm, etc., and of course, it may be other values ​​within the above range, and the present application is not limited thereto. It is understood that when the flow rate of the gaseous carbon source is increased, the thickness of the carbon shell layer 12 increases, and the tensile strength and elastic modulus of the carbon shell layer 12 further increase, and when the flow rate of the gaseous carbon source exceeds 250sccm, the carbon shell layer 12 grows faster, has more defects, and has a lower tensile modulus and elastic modulus.

[0050] In some embodiments, the temperature of the first heat treatment is 600°C to 1000°C. Specifically, the temperature of the first heat treatment may be, for example, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, and 1000°C, and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0051] In some embodiments, the incubation time of the first heat treatment is 1 min to 30 min. Specifically, the incubation time of the first heat treatment may be, for example, 1 min, 5 min, 10 min, 20 min, 30 min, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0052] In some embodiments, hydrogen gas is introduced in the first heat treatment process, and the flow rate of hydrogen gas is 10 sccm to 290 sccm. For example, the flow rate of hydrogen gas may be 10 sccm, 30 sccm, 50 sccm, 80 sccm, 90 sccm, 150 sccm, 200 sccm, 250 sccm, 290 sccm, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto. By controlling the flow rate of hydrogen gas introduction within the above range, the decomposition of the carbon source is reduced, the concentration of decomposed carbon atoms is reduced, and the rate at which carbon atoms generate a carbon shell layer is slowed down, the content of defect sites is reduced, and the I of the negative electrode material is improved. D / I Gcan be controlled to be greater than 0.5.

[0053] In some embodiments, the metal catalyst particle-supported silicon-oxygen source is obtained by subjecting the mixture including the silicon-oxygen source and the metal salt catalyst to a second heat treatment in a reducing atmosphere to obtain the metal catalyst particle-supported silicon-oxygen source. Specifically, as shown in FIG. 5, a mixed material containing a silicon oxygen source and a metal salt catalyst is The method includes the steps of mixing a solvent, a silicon-oxygen source and a metal salt catalyst to obtain a mixture, and drying and polishing the mixture to obtain a silicon-oxygen source supported by metal catalyst particles, with the understanding that the material obtained after the drying process is a clumpy solid and needs to be further polished into a powder for preliminary use.

[0054] In this step, as shown in Fig. 6, the catalytic metal ions in the mixture containing silicon oxygen raw material and metal salt catalyst are reduced to catalytic metal nanoparticles in a reducing gas atmosphere, so that on the one hand, the silicon oxygen raw material can be used as a template agent to provide the metal salt catalyst with a supporting site, and on the other hand, the silicon oxygen raw material can be used as a dispersant agent to limit the fusion of metal nanoparticles during the process of reducing and growing catalytic metal ions to metal nanoparticles, so that the catalytic metal nanoparticles have a relatively uniform and controllable size. Of course, the present application can also obtain the silicon oxygen raw material supported by metal catalyst particles by other conventional methods, for example, by directly mixing the metal catalyst particles and the silicon oxygen raw material by dry or wet process, and the present application is not limited thereto, and the metal catalyst particles include at least one of iron, cobalt, nickel, copper, gold, iron alloy, cobalt alloy, nickel alloy, copper alloy and gold alloy.

[0055] In some embodiments, the silicon oxygen source comprises at least one of silicon dioxide and silicon monoxide.

[0056] In some embodiments, the median diameter of the silicon oxygen source is 5 nm to 200 nm. Specifically, the median diameter of the silicon oxygen source may be, for example, 5 nm, 10 nm, 20 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0057] In some embodiments, the metal salt catalyst is Fe 3+ , Co 2+ , Ni 2+ , Cu 2+ and Au 3+ Illustratively, the metal salt catalyst includes at least one of Fe(NO3)3, FeCl3, Co(NO3)2, CoCl2, Ni(NO3)2, NiCl2, Cu(NO3)2, CuCl2, and HAuCl4.

[0058] In some embodiments, the mass ratio of silicon oxygen raw material to metal salt catalyst is 1: (0.08-5), specifically, the mass ratio of silicon oxygen raw material to metal salt catalyst may be 1:0.08, 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, etc., or may be other values ​​within the above range, and the present application is not limited thereto.

[0059] In some embodiments, the solvent comprises at least one of methanol, ethanol, propanol, and water.

[0060] In some embodiments, the amount of solvent added is 50 times to 1000 times the total mass of silicon oxygen source and metal salt catalyst. Specifically, the amount of solvent added is 50 times, 100 times, 200 times, 500 times, 700 times, 800 times, 900 times, 1000 times, etc., the total mass of silicon oxygen source and metal salt catalyst, and of course, other values ​​within the above range may be used, and the present application is not limited thereto.

[0061] In some embodiments, the mixing method includes at least one of grinding and ultrasonic waves, and for example, the ultrasonic power is 40W to 50W, and the ultrasonic power can be, for example, 40W, 42W, 45W, 48W, and 50W, and of course, can be other values ​​within the above range, and the present application is not limited thereto. The ultrasonic warming time is 0.5h to 5h, and the ultrasonic warming time can be, for example, 0.5h, 1h, 2h, 3h, 4h, and 5h, and of course, can be other values ​​within the above range, and the present application is not limited thereto. Within the above range, the silicon oxygen raw material and the metal salt catalyst can be sufficiently mixed, which is advantageous to the formation of the silicon oxygen raw material that uniformly supports the metal salt catalyst particles.

[0062] In some embodiments, the mode of drying comprises evaporative drying.

[0063] In some embodiments, the reducing gas atmosphere includes at least one of hydrogen gas and ammonia gas.

[0064] In some embodiments, the introduction flow rate of the reducing gas atmosphere is 10 sccm to 150 sccm. Specifically, the introduction flow rate of the reducing gas atmosphere may be, for example, 10 sccm, 30 sccm, 50 sccm, 80 sccm, 100 sccm, 120 sccm, and 150 sccm, and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0065] In some embodiments, the temperature of the second heat treatment is 400°C to 1000°C. Specifically, the temperature of the second heat treatment may be, for example, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0066] In some embodiments, the incubation time of the second heat treatment is 5 min to 30 min. Specifically, the incubation time of the second heat treatment may be, for example, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0067] In some embodiments, the heating rate of the second heat treatment is 100°C / h to 1200°C / h. Specifically, the heating rate of the second heat treatment is 100°C / h, 300°C / h, 500°C / h, 800°C / h, 1000°C / h, 1200°C / h, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0068] In step S200, as shown in Fig. 7, the first precursor is etched to obtain a second precursor, and the etching agent of the etching process includes an oxidizing acid. The second precursor includes a carbon material 1, the carbon material 1 includes a carbon shell layer 12, the carbon shell layer 12 has a chamber 11, the carbon shell layer 12 has a hole 13, and the silicon oxygen raw material is filled between the carbon material 1.

[0069] In this step, the first precursor is etched so that the catalytic metal particles inside the carbon shell layer 12 are etched, thereby forming chambers 11 and holes 13, and during the etching process, some silicon oxygen raw material can enter the chambers 11 and / or holes 13.

[0070] In some embodiments, the oxidizing acid includes at least one of sulfuric acid, nitric acid, and hydrogen peroxide. On the one hand, the oxidizing acid can be used to etch the catalytic metal particles inside the carbon shell layer 12 to form the chambers 11, and on the other hand, the oxidizing acid can cause an oxidation-reduction reaction with defects in the carbon material 1 to form bonds such as CO, C=O, CN, and CS to form holes 13. For example, a mixed acid of sulfuric acid and nitric acid can be used as an etching agent to etch metal catalytic particles made of a material that is difficult to corrode, such as iron, cobalt, iron alloy, and cobalt alloy, and a heat treatment can be performed during the etching process as necessary to improve the corrosion effect.

[0071] In some embodiments, the concentration of sulfuric acid in the mixed acid is 0.1 mol / L to 4 mol / L. Specifically, the concentration of sulfuric acid in the mixed acid is 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, etc., and of course, may be other values ​​within the above range, and is not limited in the present application.

[0072] In some embodiments, the concentration of nitric acid in the mixed acid is 0.1 mol / L to 4 mol / L. Specifically, the concentration of nitric acid in the mixed acid is 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0073] In some embodiments, the etching time is 2h to 24h, specifically, the etching time is 2h, 5h, 10h, 12h, 15h, 18h, 20h, 24h, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0074] In some embodiments, the material obtained after the etching process is a solid-liquid mixed phase, and the material obtained by the etching process needs to be solid-liquid separated, and the solid obtained thereby is first washed with water and first dried to obtain a second precursor. The second precursor includes a carbon material 1, and a chamber 11 is etched inside the shell layer structure of the carbon material 1, and a hole 13 is etched in the shell layer structure of the carbon material 1, which can ensure sufficient space to withstand the expansion stress caused by lithium insertion, thereby improving the expansion resistance performance of the negative electrode material 10.

[0075] In some embodiments, the solid-liquid separation may be, for example, centrifugation or filtration.

[0076] In some embodiments, the first water washing is performed once or more, and preferably, the first water washing is performed three to ten times.

[0077] In some embodiments, the temperature of the first drying is 50°C to 80°C. Specifically, the temperature of the first drying may be 50°C, 60°C, 70°C, 80°C, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0078] In some embodiments, the time for the first drying is 6h to 24h, specifically, the time for the first drying is 6h, 8h, 10h, 12h, 15h, 18h, 20h, 24h, etc., and of course, it may be other values ​​within the above range, and the present application is not limited thereto.

[0079] In step S300, at least a part of the silicon oxygen raw material in the second precursor is reduced to a silicon material to obtain an anode material 10, specifically, as shown in FIG. 8, the silicon oxygen raw material in the second precursor is mixed with a reducing agent and then a third heat treatment is performed, so that the silicon oxygen raw material in the second precursor can be reduced to a silicon material 2, and the simulation structure of the obtained anode material 10 is shown in FIG. 9.

[0080] In some embodiments, the reducing agent comprises at least one of magnesium powder and aluminum powder, and the silicon-oxygen raw material in the second precursor is reduced to silicon material 2 under the reducing action of the reducing agent, and the silicon-oxygen raw material does not need to be etched, thereby improving the capacity of the negative electrode material 10 and reducing the waste of resources.

[0081] In some embodiments, the mass ratio of the second precursor to the reducing agent is (1.25-2.00):1, specifically, the mass ratio of the second precursor to the reducing agent may be 1.25:1, 1.50:1, 1.75:1, 2.00:1, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto. Within the above range, the silicon-oxygen raw material can be reduced to the silicon material 2 as quickly as possible, which contributes to improving the capacity of the negative electrode material 10.

[0082] In some embodiments, the third heat treatment is performed in an inert gas atmosphere.

[0083] In some embodiments, the inert gas comprises at least one of nitrogen gas and argon gas.

[0084] In some embodiments, the temperature of the third heat treatment is 600°C to 800°C. Specifically, the temperature of the third heat treatment may be 600°C, 630°C, 650°C, 680°C, 700°C, 730°C, 750°C, 780°C, 790°C, 800°C, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0085] In some embodiments, the incubation time of the third heat treatment is 0.5 h to 5 h. Specifically, the incubation time of the third heat treatment may be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0086] In some embodiments, after the third heat treatment, the method further includes a step of passivating the material obtained by the third heat treatment to passivate the silicon material 2, reduce oxidation of the silicon material 2, and improve the capacity of the material.

[0087] In some embodiments, the gas to be deactivated comprises ammonia gas.

[0088] In some embodiments, the method further comprises, after the passivation treatment, subjecting the material resulting from the passivation treatment to an acid wash, a second water rinse, and a second drying step.

[0089] In some embodiments, the pickling reagent comprises hydrochloric acid.

[0090] In some embodiments, the pickling time is 2h to 24h. Specifically, the pickling time may be, for example, 2h, 5h, 8h, 10h, 12h, 15h, 18h, 24h, etc., and of course, may be other values ​​within the above range, and the present application is not limited thereto.

[0091] In some embodiments, the second water wash is performed 5 to 10 times.

[0092] In some embodiments, the second mode of drying comprises lyophilization.

[0093] In a third aspect, the present application provides a lithium ion battery including the negative electrode material 10 described above or the negative electrode material 10 produced by the method described above.

[0094] It is obvious to those skilled in the art that the above-described method for manufacturing a lithium-ion battery is merely an example, and other methods commonly used in the art may be adopted without departing from the scope of the present invention.

[0095] The present invention will be further described below by dividing it into several embodiments. However, the present invention is not limited to the following specific embodiments. They may be modified as appropriate without changing the scope of the main claims.

[0096] Example 1

[0097] (1) To 800 mL of methanol, first add 1 g of SiO2, then add 2.10 g of Co(NO3). 2· After adding 6H2O to obtain a mixed solution, the mixed solution was ultrasonicated for 4h with an ultrasonic power of 40W. Then, the mixed solution after ultrasonication was evaporated and dried for 12h to obtain a lumpy solid. Finally, the lumpy solid was crushed into powder to obtain the catalyst Co. 2+ The silicon dioxide supported on SiO2@Co is obtained.

[0098] (2) The SiO2@Co powder from (1) is placed in a CVD tube furnace, and heated to 800 °C at a heating rate of 1,200 °C / h in a H2 environment with a flow rate of 90 sccm. The temperature is then kept at that temperature for 20 min to reduce the SiO2@Co to form silicon dioxide powder carrying cobalt nanoparticles (SiO2-CoNPs).

[0099] (3) Under high temperature conditions at 800°C, the H2 flow rate is adjusted to 10 sccm, and methane at a flow rate of 150 sccm is introduced. After 10 min of introduction, H2 and methane are turned off, Ar gas is introduced, and the temperature is lowered to room temperature to obtain silicon dioxide SiO2-Co@GNPs powder carrying multilayer graphite-encapsulated cobalt nanoparticles.

[0100] (4) The SiO2-Co@GNPs powder was placed in a mixed acid solution of 1 mol / L sulfuric acid and 1 mol / L nitric acid, etched for 8 h, and centrifuged to obtain porous hollow graphite-supported silicon dioxide SiO2-MGNPs precipitates. The precipitates were washed with water multiple times and then dried for 8 h to obtain SiO2-MGNPs powder.

[0101] (5) SiO2-MGNPs powder and magnesium powder are mixed in a mass ratio of 1.5:1, placed in a high-temperature tubular furnace, and subjected to a high-temperature reduction reaction in an Ar gas atmosphere at 650°C for 2 hours, after which the temperature is lowered to room temperature. Next, ammonia gas is introduced for 1 hour, and then the ammonia gas is closed, and Ar gas is introduced for another 0.5 hours, and then the Ar gas is closed and the mixed powder is taken out. Finally, the mixed powder is pickled in 1 mol / L hydrochloric acid for 2 hours, centrifuged, washed with water, and freeze-dried to obtain Si-MGNPs powder.

[0102] The negative electrode material produced in this embodiment includes a spherical carbon material and a silicon material located between the carbon materials, the carbon material includes a carbon shell layer that surrounds the carbon shell layer to form a chamber, the carbon shell layer has holes, the carbon shell layer includes multiple layers of graphitized carbon material, and the multiple layers of graphitized carbon material are stacked along the radial direction of the carbon material. The number of layers of the graphitized carbon material in the carbon shell layer, the thickness of the carbon shell layer, the average inner diameter of the chamber, the average pore size of the holes, and the porosity and thickness of the negative electrode material are shown in Table 1.

[0103] Example 2

[0104] The difference from Example 1 is that Co(NO3) in step (1) 2· The solution is to replace 6H2O with Cu(NO3)2.

[0105] The negative electrode material produced in this embodiment includes a carbon material and a silicon material located between the carbon materials, the carbon material includes a carbon shell layer, the carbon shell layer surrounds the chamber, the carbon shell layer has holes, the carbon shell layer includes a graphitized carbon material, the graphitized carbon material has a layered structure, and the layered structure of the graphitized carbon material is stacked along the radial direction of the carbon material. The number of layers of the graphitized carbon material of the carbon shell layer, the thickness of the carbon shell layer, the average inner diameter of the chamber, the average pore size of the holes, and the porosity and thickness of the negative electrode material are shown in Table 1.

[0106] Example 3

[0107] The difference from Example 1 is that Co(NO3) in step (1) 2· The solution is to replace 6H2O with Fe(NO3)3.

[0108] The negative electrode material produced in this embodiment includes a carbon material and a silicon material located between the carbon materials, the carbon material includes a carbon shell layer, the carbon shell layer surrounds the chamber, the carbon shell layer has holes, the carbon shell layer includes a graphitized carbon material, the graphitized carbon material has a layered structure, and the layered structure of the graphitized carbon material is stacked along the radial direction of the carbon material. The number of layers of the graphitized carbon material of the carbon shell layer, the thickness of the carbon shell layer, the average inner diameter of the chamber, the average pore size of the holes, and the porosity and thickness of the negative electrode material are shown in Table 1.

[0109] Example 4

[0110] The difference from Example 1 is that Co(NO3) in step (1) 2· The solution is to replace 6H2O with NiCl2.

[0111] The negative electrode material produced in this embodiment includes a carbon material and a silicon material located between the carbon materials, the carbon material includes a carbon shell layer, the carbon shell layer surrounds the chamber, the carbon shell layer has holes, the carbon shell layer includes a graphitized carbon material, the graphitized carbon material has a layered structure, and the layered structure of the graphitized carbon material is stacked along the radial direction of the carbon material. The number of graphene layers of the carbon shell layer, the thickness of the carbon shell layer, the average inner diameter of the chamber, the average pore size of the holes, and the porosity and thickness of the negative electrode material are shown in Table 1.

[0112] Example 5

[0113] The difference from Example 1 is that steps (1) and (2) were not performed, and 1 g of silicon dioxide, 0.43 g of cobalt metal nanoparticles, and 800 ml of methanol were mixed, and then ultrasonicated for 4 hours at an ultrasonic power of 40 W. After drying, silicon dioxide SiO2-CoNPs powder carrying cobalt nanoparticles was obtained. The obtained SiO2-CoNPs was further subjected to steps (3) to (5) of Example 1.

[0114] The negative electrode material produced in this embodiment includes a carbon material and a silicon material located between the carbon materials, the carbon material includes a carbon shell layer, the carbon shell layer surrounds the chamber, the carbon shell layer has holes, the carbon shell layer includes a graphitized carbon material, the graphitized carbon material has a layered structure, and the layered structure of the graphitized carbon material is stacked along the radial direction of the carbon material. The number of graphene layers of the carbon shell layer, the thickness of the carbon shell layer, the average inner diameter of the chamber, the average pore size of the holes, and the porosity and thickness of the negative electrode material are shown in Table 1.

[0115] Example 6

[0116] (1) To 800 mL of methanol, first add 1 g of SiO2, then add 2.10 g of Co(NO3). 2· 6H2O and 20mg phenylalanine (Phe) are added to obtain a mixed solution, and then the mixed solution is ultrasonicated for 4h with an ultrasonic power of 40W. Then, the mixed solution after ultrasonication is evaporated and dried for 12h to obtain a lumpy solid. Finally, the lumpy solid is ground into powder to obtain the catalyst Co. 2+ And silicon dioxide SiO2@Co-Phe supporting the solid carbon source Phe is obtained.

[0117] (2) The SiO2@Co-Phe powder from (1) is placed in a CVD tube furnace, and heated to 800 °C at a heating rate of 1200 °C / h in a H2 environment with a flow rate of 90 sccm, and then kept at that temperature for 20 min to reduce the SiO2@Co to form silicon dioxide SiO2-CoNPs powder carrying cobalt nanoparticles (during this process, the solid carbon source Phe has already begun to decompose).

[0118] (3) Under high temperature conditions at 800 °C, the H2 flow rate was adjusted to 10 sccm to continue the decomposition process of Phe. After 10 min, H2 was turned off, Ar gas was introduced, and the temperature was lowered to room temperature to obtain silicon dioxide SiO2-Co@GNPs powder carrying multi-layer graphite-encapsulated cobalt nanoparticles.

[0119] (4) The SiO2-Co@GNPs powder was placed in a mixed acid solution of 1 mol / L sulfuric acid and 1 mol / L nitric acid, etched for 8 h, and centrifuged to obtain porous hollow graphite-supported silicon dioxide SiO2-MGNPs precipitates. The precipitates were washed with water multiple times and then dried for 8 h to obtain SiO2-MGNPs powder.

[0120] (5) SiO2-MGNPs powder and magnesium powder are mixed in a mass ratio of 1.5:1, placed in a high-temperature tubular furnace, and subjected to a high-temperature reduction reaction in an Ar gas atmosphere at 650°C for 2 hours, after which the temperature is lowered to room temperature. Next, ammonia gas is introduced for 1 hour, and then the ammonia gas is closed, and Ar gas is introduced for another 0.5 hours, and then the Ar gas is closed and the mixed powder is taken out. Finally, the mixed powder is pickled in 1 mol / L hydrochloric acid for 2 hours, centrifuged, washed with water, and freeze-dried to obtain Si-MGNPs powder.

[0121] The negative electrode material produced in this embodiment includes a carbon material and a silicon material located between the carbon materials, the carbon material includes a carbon shell layer, the carbon shell layer surrounds the chamber, the carbon shell layer has holes, the carbon shell layer includes a graphitized carbon material, the graphitized carbon material has a layered structure, and the layered structure of the graphitized carbon material is stacked along the radial direction of the carbon material. The number of graphene layers of the carbon shell layer, the thickness of the carbon shell layer, the average inner diameter of the chamber, the average pore size of the holes, and the porosity and thickness of the negative electrode material are shown in Table 1.

[0122] Example 7

[0123] The difference from Example 1 is that the flow rate of methane introduced is 8 sccm, and the introduction and warming time is 5 minutes.

[0124] The negative electrode material produced in this embodiment includes a carbon material and a silicon material located between the carbon materials, the carbon material includes a carbon shell layer, the carbon shell layer surrounds a chamber, the carbon shell layer has holes, the carbon shell layer includes multiple layers of graphene, and the multiple layers of graphene are stacked along the radial direction of the carbon material. The number of graphene layers of the carbon shell layer, the thickness of the carbon shell layer, the average inner diameter of the chamber, the average pore size of the holes, and the porosity and thickness of the negative electrode material are shown in Table 1.

[0125] Example 8

[0126] The difference from Example 1 is that the methane introduction flow rate is 10 sccm and the introduction and warming time is 30 minutes.

[0127] The negative electrode material produced in this embodiment includes a carbon material and a silicon material located between the carbon materials, the carbon material includes a chamber carbon shell layer, the carbon shell layer has a chamber, the carbon shell layer has a hole, the carbon shell layer includes a graphitized carbon material, the graphitized carbon material has a layered structure, and the layered structure of the graphitized carbon material is stacked along the radial direction of the carbon material. The number of graphene layers of the carbon shell layer, the thickness of the carbon shell layer, the average inner diameter of the chamber, the average pore size of the hole, the porosity and thickness of the negative electrode material are shown in Table 1.

[0128] Example 9

[0129] The difference from Example 1 is that the methane introduction flow rate is 50 sccm and the introduction and warming time is 20 minutes.

[0130] The negative electrode material produced in this embodiment includes a carbon material and a silicon material located between the carbon materials, the carbon material includes a chamber carbon shell layer, the carbon shell layer has a chamber, the carbon shell layer has a hole, the carbon shell layer includes a graphitized carbon material, the graphitized carbon material has a layered structure, and the layered structure of the graphitized carbon material is stacked along the radial direction of the carbon material. The number of graphene layers of the carbon shell layer, the thickness of the carbon shell layer, the average inner diameter of the chamber, the average pore size of the hole, the porosity and thickness of the negative electrode material are shown in Table 1.

[0131] Example 10

[0132] The difference from Example 1 is that the methane introduction flow rate is 250 sccm and the introduction warming time is 1 minute.

[0133] The negative electrode material produced in this embodiment includes a carbon material and a silicon material located between the carbon materials, the carbon material includes a chamber carbon shell layer, the carbon shell layer has a chamber, the carbon shell layer has a hole, the carbon shell layer includes a graphitized carbon material, the graphitized carbon material has a layered structure, and the layered structure of the graphitized carbon material is stacked along the radial direction of the carbon material. The number of graphene layers of the carbon shell layer, the thickness of the carbon shell layer, the average inner diameter of the chamber, the average pore size of the hole, the porosity and thickness of the negative electrode material are shown in Table 1.

[0134] Example 11

[0135] The difference from Example 1 is that the methane introduction flow rate is 300 sccm and the introduction warming time is 10 minutes.

[0136] The negative electrode material produced in this embodiment includes a carbon material and a silicon material located between the carbon materials, the carbon material includes a chamber carbon shell layer, the carbon shell layer has a chamber, the carbon shell layer has a hole, the carbon shell layer includes a graphitized carbon material, the graphitized carbon material has a layered structure, and the layered structure of the graphitized carbon material is stacked along the radial direction of the carbon material. The number of graphene layers of the carbon shell layer, the thickness of the carbon shell layer, the average inner diameter of the chamber, the average pore size of the hole, the porosity and thickness of the negative electrode material are shown in Table 1.

[0137] Comparative Example 1

[0138] (1) After uniformly mixing 1g SiO2 powder and 0.5g pitch powder, the mixed powder is placed in a high-temperature box furnace and heated to 800°C at a heating rate of 1200°C / h under a N2 atmosphere, and then kept at a constant temperature for 10 minutes to carbonize the powder, forming carbon-sealed silicon dioxide SiO2-C powder.

[0139] (2) The SiO2-C powder is placed in a mixed acid solution of 1 mol / L sulfuric acid and 1 mol / L nitric acid, etched for 8 hours, and centrifuged to obtain a porous carbon-coated silicon dioxide SiO2-MCNPs precipitate. The SiO2-MCNPs precipitate is then placed in 20 wt% hydrofluoric acid to etch the silicon dioxide for 8 hours to obtain a porous carbon material MCNPs powder.

[0140] (3) MGNPs powder, SiO2 and magnesium powder are mixed in a mass ratio of 1:2:2, placed in a high-temperature tubular furnace, and subjected to a high-temperature reduction reaction in a N2 atmosphere at 650°C for 2 hours, after which the temperature is lowered to room temperature. Next, ammonia gas is introduced for 1 hour, and then the ammonia gas is closed, and N2 is introduced for another 0.5 hours, and then the N2 is closed and the mixed powder is taken out. Finally, the mixed powder is pickled in 1 mol / L hydrochloric acid for 2 hours, centrifuged, washed with water, and freeze-dried to obtain Si-MCNPs powder.

[0141] The negative electrode material produced in this comparative example includes a carbon material and a silicon material located between the carbon materials, the carbon material includes a carbon shell layer, the carbon shell layer has a chamber, the carbon shell layer has a hole, and the carbon shell layer is amorphous carbon. The thickness of the carbon shell layer, the average inner diameter of the chamber, the average pore diameter of the hole, the porosity and thickness of the negative electrode material are shown in Table 1.

[0142] Comparative Example 2

[0143] The difference from Example 1 is that the mixed acid solution of 1 mol / L sulfuric acid and 1 mol / L nitric acid in step (4) is replaced with HF.

[0144] The negative electrode material produced in this comparative example includes graphite particles and silicon material located between the graphite particles, and the graphite particles include a solid metal core and a graphite shell layer located on the surface of the solid metal core. The measurement parameters of the negative electrode material are shown in Table 1.

[0145] Performance measurement

[0146] (1) The pore volume dimensions of the chambers and holes are measured using BET pore distribution, and the porosity of the carbon material and the porosity of the negative electrode material are calculated. Before measuring the porosity of the carbon material, the silicon material in the negative electrode material needs to be etched away with HF.

[0147] (2) Before etching the silicon material in the negative electrode material, the mass M1 of the negative electrode material is measured, and after etching the silicon material using HF, the mass M2 of the negative electrode material is measured, where (M2-M1) / M2 is the mass ratio of the silicon material in the negative electrode material.

[0148] (3) Using a high-resolution transmission electron microscope, the number of graphene layers in the carbon shell layer, the thickness of the carbon shell layer, and the distance between adjacent carbon materials are measured.

[0149] (4) After etching the silicon material in the negative electrode material using HF, the sphericity and median diameter of the carbon material are measured using a Zetasizer.

[0150] (5) After etching the silicon material in the negative electrode material using HF, the elastic modulus and tensile strength of the carbon material are measured using a nanoindenter.

[0151] (6) Measuring π-π stacking van der Waals forces between carbon materials using a dual polarization interferometer

[0152] (7) Method for measuring the average chamber pore size: The pore sizes of 200 chambers in a carbon material in a transmission electron microscope image are mathematically statistically analyzed to calculate the average value.

[0153] (8) Measurement method of average pore size: After etching the silicon material in the negative electrode material with HF, the average pore size of the holes is measured with the American Micromeritics ASAP 2460 fully automatic specific surface and porosity analyzer, and the gas used during measurement is CO2.

[0154] (9) Method for measuring the median diameter of silicon material: The diameter of silicon material in a transmission electron microscope image is mathematically calculated.

[0155] (10) Measure the electrochemical properties of the negative electrode material using the following method. The prepared silicon-carbon anode material, conductive agent and adhesive are mixed with a solvent in a mass ratio of 94:1:5 to form a slurry (solid content 50%), which is applied to a copper foil current collector and vacuum dried to prepare an anode piece; then the anode piece, the ternary cathode piece prepared by the conventional maturation process, 1mol / L LiPF6 / ethylene carbonate + dimethyl carbonate + ethyl methyl carbonate (v / v=1:1:1) electrolyte, Celgard2400 separator and battery housing are assembled into an 18650 cylindrical cell by a conventional manufacturing process. The charge and discharge test of the cylindrical battery is performed with a LAND battery test system manufactured by Wuhan LAND electronics Co., Ltd., and the conditions are constant current charging and discharging at 0.2C at room temperature, and the charge and discharge voltage is 2.75V to 4.2V. The test results are shown in Tables 1 and 2.

[0156] [Table 1]

[0157] [Table 2]

[0158] As shown in Tables 1 and 2, in the manufacturing method shown in Examples 1 to 11 of the present application, under the first heat treatment conditions, the carbon source is catalytically grown into the carbon shell layer 12 through the metal catalyst particles, and further, by the etching process, the carbon shell layer 12 has a chamber 11 inside its structure, and holes 13 are formed in the carbon shell layer 12, so that the carbon material has a large pore volume and lithium insertion ability, thereby improving the expansion resistance of the carbon material. In addition, in the manufacturing method of the present application, there is no need to etch the silicon oxygen raw material, and the silicon oxygen raw material is directly reduced to a silicon material, which reduces the waste of the silicon oxygen raw material and improves the capacity of the negative electrode material.

[0159] In Example 1 and Examples 7 to 11, the present application adjusts the thickness of the generated carbon shell layer 12 (i.e., the number of graphene layers in the carbon shell layer 12) by adjusting the introduction flow rate of the gas phase carbon source in step (3) and the incubation time of the first heat treatment. In Example 7, the introduction flow rate of the gas phase carbon source is low, so the thickness of the carbon shell layer 12 is thin and the tensile strength of the carbon material 1 is reduced, thereby reducing the cycle performance and expansion resistance of the negative electrode material 10. In Example 11, the introduction flow rate of the gas phase carbon source is too high, so the thickness of the carbon shell layer 12 is thick and the tensile strength of the carbon material 1 is increased, but the flexibility is reduced, the gaps between the carbon materials 1 are reduced, the amount of the silicon material 2 is reduced, and the capacity of the negative electrode material 10 is reduced.

[0160] In the negative electrode material produced in Comparative Example 1, catalytic metal particles were not added, and therefore the resulting carbon material was amorphous carbon that did not have a continuous graphite crystal lattice structure. As a result, the mechanical performance of the resulting negative electrode material was poor, and furthermore, the expansion resistance and cycle stability were poor.

[0161] In Comparative Example 2, the etching process is performed using HF, and the carbon shell layer can block HF, so that there are no chambers or holes in the carbon material, and the content of silicon material in the material is reduced by HF etching, which further deteriorates the specific capacity of the material. If there are no chambers or holes, the volume expansion of the material will increase, but since the amount of silicon in the negative electrode material obtained in this Comparative Example is small, the overall volume expansion is relatively small.

[0162] The above is only a preferred embodiment of the present application, and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and changes. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present application should be included in the protection scope of the present application. [Explanation of symbols]

[0163] 10-Anode Materials 1-Carbon Materials 11-Chamber 12-Carbon shell layer 13-hole 14-Graphitized carbon materials 2-Silicon Materials

Claims

1. A negative electrode material comprising: The negative electrode material comprises a carbon material, the carbon material comprising a carbon shell layer, the carbon material having a chamber inside, the chamber being formed so as to be surrounded by the carbon shell layer, the carbon shell layer having holes, and at least some of the holes penetrating the carbon shell layer.

2. 2. The negative electrode material according to claim 1, wherein the carbon material is spherical, the carbon shell layer contains a graphitized carbon material, the graphitized carbon material has a layered structure, and the layered structure of the graphitized carbon material is stacked along a radial direction of the carbon material.

3. 3. The negative electrode material according to claim 1, further comprising a silicon material, the silicon material being distributed within the carbon material.

4. 4. The negative electrode material of claim 3, wherein at least a portion of the silicon material is located between the carbon shell layers.

5. 4. The negative electrode material of claim 3, wherein a portion of the silicon material is located in the chamber and / or the pore.

6. The negative electrode material according to claim 1, characterized in that the negative electrode material satisfies at least one of the following characteristics (1) to (13). (1) lamellar graphite is provided between the carbon materials; (2) at least some of the pores extend through the carbon shell layer; (3) the median diameter of the carbon material is 5 nm to 200 nm; (4) the number of layers of the graphitized carbon material in the carbon shell layer is less than 20; (5) the thickness of the carbon shell layer is 1.2 nm to 5.2 nm; (6) The negative electrode material has a Raman spectrum obtained by Raman spectroscopy using a measurement light source having a wavelength of 532 nm, and the Raman spectrum has a wavelength of 1300 -1 ~1400 -1 The D band was observed at 1500 -1 ~1600 -1 The G band was observed at 0.05 and the D band peak intensity was I D and the G-band peak intensity I G Comparison with I G / I D is greater than 0.5; (7) the average inner diameter of the chamber is 3.8 nm to 198.8 nm; (8) the average pore size of the pores is 0.42 nm to 2 nm; (9) the distance between adjacent carbon materials is 0 nm to 40 nm; (10) The sphericity of the carbon material is 0.6 to 1; (11) The silicon material is 5% by mass to 80% by mass with respect to the negative electrode material; (12) The median diameter of the silicon material is 1 nm to 15 nm; (13) The silicon material includes at least one of crystalline silicon and amorphous silicon.

7. The negative electrode material according to claim 1, characterized in that the negative electrode material satisfies at least one of the following characteristics (1) to (5). (1) the elastic modulus of the carbon material is 0.1 TPa to 0.8 TPa; (2) the tensile strength of the carbon material is 15 GPa to 110 GPa; (3) the porosity of the carbon material is 65% to 96%; (4) the porosity of the negative electrode material is 7% to 50%; (5) The π-π stacking van der Waals force between adjacent carbon materials is 1 kJ / mol to 50 kJ / mol.

8. A method for producing a negative electrode material, comprising the steps of: A first heat treatment is performed on a mixture including a silicon-oxygen source supported by metal catalyst particles and a carbon source to catalyze the graphitization of the carbon source and obtain a first precursor; Etching the first precursor to obtain a second precursor, the etchant of the etching process being an oxidizing acid; The method for producing an anode material includes reducing at least a portion of the silicon-oxygen source in the second precursor to a silicon material to obtain an anode material.

9. 9. The method according to claim 8, wherein the metal catalyst particle-supported silicon-oxygen raw material is produced by the following method. The mixture containing the silicon / oxygen source and the metal salt catalyst is subjected to a second heat treatment in a reducing atmosphere to obtain the silicon / oxygen source supported by the metal catalyst particles.

10. The method according to claim 9, characterized in that at least one of the following characteristics (1) to (14) is satisfied. (1) the silicon-oxygen source contains at least one of silicon dioxide and silicon monoxide; (2) the median diameter of the silicon / oxygen source is 5 nm to 200 nm; (3) The metal salt catalyst is Fe 3+ , Co 2+ , Ni 2+ , Cu 2+ and Au 3+ containing at least one of the following: (4) The metal salt catalyst is Fe(NO 3 ) 3 , FeCl 3 , Co(NO 3 ) 2 , CoCl 2 , Ni(NO 3 ) 2 , NiCl 2 , Cu(NO 3 ) 2 , CuCl 2 and HAuCl 4 containing at least one of the following: (5) the mass ratio of the silicon oxygen source to the metal salt catalyst is 1:(0.08-5.00); (6) the mixture containing the silicon oxygen source and the metal salt catalyst further contains a solvent; (7) The mixture containing the silicon oxygen source and the metal salt catalyst further contains a solvent, and the solvent contains at least one of methanol, ethanol, propanol, and water; (8) The mixture containing the silicon oxygen source and the metal salt catalyst further contains a solvent, and the amount of the solvent added is 50 to 1000 times the total mass of the silicon oxygen source and the metal salt catalyst; (9) The method further includes a step of drying and polishing the mixture containing the silicon oxygen source and the metal salt catalyst before performing a second heat treatment; (10) The reducing atmosphere contains at least one of hydrogen gas and ammonia gas; (11) The introduction flow rate of the reducing atmosphere is 10 sccm to 150 sccm; (12) The temperature of the second heat treatment is 400° C. to 1000° C.; (13) The warming time of the second heat treatment is 5 minutes to 30 minutes; (14) The temperature increase rate of the second heat treatment is 100° C. / h to 1200° C. / h.

11. The method according to claim 8, characterized in that at least one of the following characteristics (1) to (9) is satisfied. (1) The carbon source includes a gas phase carbon source and a solid phase carbon source; (2) the carbon source includes a gas phase carbon source and a solid phase carbon source, the gas phase carbon source including at least one of methane, ethane, and acetylene; (3) The carbon source includes a gas phase carbon source and a solid phase carbon source, and the solid phase carbon source includes at least one of pitch, glucose, sucrose, cellulose, glycine, alanine, and phenylalanine; (4) The carbon source includes a gas phase carbon source and a solid phase carbon source, and the mass ratio of the solid phase carbon source to the metal catalyst particles is 1:(10 to 10,000); (5) The carbon source includes a gas phase carbon source and a solid phase carbon source, and the gas phase carbon source is introduced at a flow rate of 10 sccm to 250 sccm; (6) The temperature of the first heat treatment is 600° C. to 1000° C.; (7) The warming time of the first heat treatment is 1 min to 30 min; (8) before subjecting the mixture containing the silicon / oxygen source and the carbon source supported by the metal catalyst particles to a first heat treatment, the method further comprises passing hydrogen gas through the mixture containing the silicon / oxygen source and the carbon source supported by the metal catalyst particles; (9) Before subjecting the mixture containing the silicon / oxygen source supported by the metal catalyst particles and the carbon source to a first heat treatment, hydrogen gas is passed through the mixture containing the silicon / oxygen source supported by the metal catalyst particles and the carbon source, and the flow rate of the hydrogen gas is 10 sccm to 90 sccm.

12. The method according to claim 8, characterized in that at least one of the following characteristics (1) to (6) is satisfied. (1) the oxidizing acid includes at least one of sulfuric acid, nitric acid, and hydrogen peroxide; (2) the oxidizing acid includes a mixed acid of sulfuric acid and nitric acid; (3) The oxidizing acid includes a mixed acid of sulfuric acid and nitric acid, and the concentration of the sulfuric acid in the mixed acid is 0.1 mol / L to 4 mol / L; (4) The oxidizing acid includes a mixed acid of sulfuric acid and nitric acid, and a concentration of the nitric acid in the mixed acid is 0.1 mol / L to 4 mol / L; (5) the etching process lasts for 2 hours to 24 hours; (6) The method further includes a step of performing a process of performing a solid-liquid separation of the second precursor, and a first water washing and a first drying of the obtained solid before reducing at least a part of the silicon oxygen raw material in the second precursor to a silicon material.

13. Reducing at least a portion of the silicon oxygen source in the second precursor to a silicon material includes performing a third heat treatment after mixing the second precursor with a reducing agent; The method according to claim 8, characterized in that at least one of the following characteristics (1) to (9) is satisfied. (1) The reducing agent contains at least one of metallic magnesium and metallic aluminum; (2) the mass ratio of the second precursor to the reducing agent is (1.25-2.00):1; (3) the third heat treatment is performed in an inert gas atmosphere; (4) The third heat treatment is performed in an inert gas atmosphere, and the inert gas contains at least one of nitrogen gas and argon gas; (5) the temperature of the third heat treatment is 600° C. to 800° C.; (6) The warming time of the third heat treatment is 0.5 h to 5 h; (7) further comprising a step of, after performing a third heat treatment on the second precursor and the reducing agent, passivating the material obtained by the third heat treatment; (8) The method further includes a step of performing a deactivation treatment on the material obtained by the third heat treatment after performing a third heat treatment on the second precursor and the reducing agent, and the gas for the deactivation treatment includes ammonia gas; (9) The method further includes the steps of: after performing a third heat treatment on the second precursor and the reducing agent, performing a passivation treatment on the material obtained by the third heat treatment; and performing an acid washing, a second water washing, and a second drying process on the material obtained by the passivation treatment.

14. A lithium ion battery comprising the negative electrode material according to any one of claims 1 to 7 or the negative electrode material produced by the method according to any one of claims 8 to 13.

Citation Information

Patent Citations

  • SiOx based composite negative electrode material, preparation method and battery

    CN103647056A

  • Lithium ion battery negative electrode active material, preparation method thereof, negative electrode and lithium ion battery comprising negative electrode

    CN107293701A

  • Silicon-based composite material with nano hierarchical structure and preparation method and application of silicon-based composite material with nano hierarchical structure

    CN108023074A

  • Porous silicon carbon negative electrode material, a preparation method thereof and a lithium ion battery

    CN109273680A

  • Positive plate-shell structure cathode material and preparation method thereof and lithium ion battery

    CN109346688A